The effect of calcium on the cohesive strength and flexural properties of low-methoxyl pectin biopolymers - Byun, Christine; Zheng, Yifan; Pierce, Aidan; Wagner, Willi Linus; Scheller, Henrik V.; Mohnen, Debra; Ackermann, Maximilian; Mentzer, Steven J. (Molecules, 2020)
Pectin binds the mesothelial glycocalyx of visceral organs, suggesting its potential role as a mesothelial sealant. To assess the mechanical properties of pectin films, we compared pectin films with a less than 50% degree of methyl esterification (low-methoxyl pectin, LMP) to films with greater than 50% methyl esterification (high-methoxyl pectin, HMP). LMP and HMP polymers were prepared by step-wise dissolution and high-shear mixing. Both LMP and HMP films demonstrated a comparable clear appearance. Fracture mechanics demonstrated that the LMP films had a lower burst strength than HMP films at a variety of calcium concentrations and hydration states. The water content also influenced the extensibility of the LMP films with increased extensibility (probe distance) with an increasing water content. Similar to the burst strength, the extensibility of the LMP films was less than that of HMP films. Flexural properties, demonstrated with the 3-point bend test, showed that the force required to displace the LMP films increased with an increased calcium concentration (p < 0.01). Toughness, here reflecting deformability (ductility), was variable, but increased with an increased calcium concentration. Similarly, titrations of calcium concentrations demonstrated LMP films with a decreased cohesive strength and increased stiffness. We conclude that LMP films, particularly with the addition of calcium up to 10 mM concentrations, demonstrate lower strength and toughness than comparable HMP films. These physical properties suggest that HMP has superior physical properties to LMP for selected biomedical applications.
Published: 24 December 2019
Gesehen am 01.04.2020